Solid electrolyte and method for producing the same

A sulfide solid electrolyte with controlled surface chemistry, produced by heating in an oxygen-containing atmosphere, addresses the resistive layer issue in solid-state batteries, enhancing their performance in high-temperature conditions.

JP2025044617APending Publication Date: 2025-04-02MITSUI MINING & SMELTING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023152301
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-04-02

AI Technical Summary

Technical Problem

The formation of a resistive layer between the active material and the solid electrolyte in solid-state batteries is easily triggered in high-temperature environments, which existing surface treatment techniques struggle to address effectively.

Method used

A sulfide solid electrolyte with specific X-ray photoelectron spectroscopy (XPS) characteristics, including peaks in defined binding energy ranges and intensity ratios, is produced by heating in an oxygen-containing atmosphere to introduce sulfite or sulfone groups on the surface, suppressing resistive layer formation.

Benefits of technology

The electrolyte effectively suppresses the increase in DC resistance of solid-state batteries in high-temperature environments, maintaining ionic conductivity and battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044617000003
    Figure 2025044617000003
  • Figure 2025044617000004
    Figure 2025044617000004
  • Figure 2025044617000001
    Figure 2025044617000001
Patent Text Reader

Abstract

To provide a sulfide solid electrolyte and a method for producing the same, which are capable of preventing the formation of a resistance layer between the active material and the solid electrolyte at elevated temperatures.SOLUTION: A solid electrolyte is provided in which a peak 1 is observed in the binding energy range of 165 eV or more to 170 eV or less, and a peak 2 is observed in the range of 155 eV or more to 166 eV or less for S2p as measured by X-ray photoelectron spectroscopy, wherein, when the peak top intensity of the peak 1 is defined as I1 and the peak top intensity of the peak 2 is defined as I2, the value of I1 / I2 is 0.017 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid electrolyte and a method for producing the same, and also to an electrode mixture, a solid electrolyte layer, and a solid-state battery each containing a solid electrolyte. [Background technology]

[0002] In recent years, secondary batteries have been attracting attention as an effort to prevent global warming by reducing CO2 emissions. Among them, all-solid-state batteries using sulfide solid electrolytes synthesized using lithium sulfide and other starting materials have been attracting attention. All-solid-state batteries using sulfide solid electrolytes do not use flammable organic solvents, so they have the advantage of being able to simplify safety devices and have excellent manufacturing costs and productivity. In addition, this type of solid electrolyte is advantageous in terms of improving safety and durability, as no ion species other than lithium ions move within the electrolyte, and side reactions due to the movement of anions do not occur.

[0003] In order to improve the properties of a sulfide solid electrolyte, a technique for modifying the surface of the electrolyte has been proposed. For example, Patent Document 1 proposes exposing particles of a solid electrolyte to an atmosphere having a dew point within a predetermined range for a predetermined time without heat treatment in order to improve the contact state between the particles of the solid electrolyte and the particles of a positive electrode active material or a negative electrode active material.

[0004] Patent Document 2 proposes exposing a sulfide solid electrolyte to a gas having a temperature higher than 100° C. and lower than 200° C. and a dew point of −60° C. or higher and −20° C. or lower, in order to reduce the generation of hydrogen sulfide from the sulfide solid electrolyte.

[0005] In Patent Document 3, in order to make a sulfide solid electrolyte less likely to ignite, the sulfide solid electrolyte is held in a dry air atmosphere for a predetermined time, and the surface of the sulfide solid electrolyte is oxidized to remove SS bonds and S bonds on the surface. 2- It has been proposed to deplete [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2019 / 176895 Brochure [Patent Document 2] JP 2020-75855 A [Patent Document 3] Patent No. 7092248 Summary of the Invention [Problem to be solved by the invention]

[0007] However, a problem with solid-state batteries containing a solid electrolyte is that a resistive layer is easily formed between the active material and the solid electrolyte in a high-temperature environment. It is not easy to solve this problem using the surface treatment techniques described in Patent Documents 1 to 3. Therefore, an object of the present invention is to provide a sulfide solid electrolyte that can suppress the formation of a resistance layer between an active material and a solid electrolyte in a high-temperature environment, and a method for producing the same. [Means for solving the problem]

[0008] The present invention relates to a method for determining the S 2p Peak 1 is observed in the binding energy range of 165 eV to 170 eV, and peak 2 is observed in the binding energy range of 155 eV to 166 eV. The peak top intensity of the peak 1 is I1, When the peak top intensity of the peak 2 is I2, The present invention provides a sulfide solid electrolyte having an I1 / I2 value of 0.017 or more.

[0009] The present invention also provides a method for producing a sulfide solid electrolyte, comprising heating a powder of the sulfide solid electrolyte in an oxygen-containing atmosphere having a dew point of −40° C. or lower. Effect of the Invention

[0010] According to the present invention, there are provided a sulfide solid electrolyte capable of suppressing an increase in DC resistance of a solid-state battery in a high-temperature environment of, for example, 70° C. or higher, and a method for producing the same. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 shows XPS spectra in the range of 165 eV to 170 eV of the sulfide solid electrolytes obtained in Example 2 and Comparative Examples 1 and 2. [Diagram 2] FIG. 2 shows XPS spectra in the range of 158 eV to 170 eV of the sulfide solid electrolytes obtained in Example 2 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described below based on its preferred embodiments. First, the sulfide solid electrolyte of the present invention will be described. As long as the sulfide solid electrolyte of the present invention has lithium ion conductivity, the type and composition of the sulfide solid electrolyte are not particularly limited, and can be appropriately selected according to the application, desired physical properties, etc. The sulfide solid electrolyte may contain, for example, lithium (Li) element and sulfur (S) element, or may contain lithium (Li) element, phosphorus (P) element and sulfur (S) element, but preferably contains lithium (Li) element, phosphorus (P) element, sulfur (S) element and halogen (X) element. Examples of the halogen (X) element include fluorine (F), chlorine (Cl), bromine (Br) element and iodine (I) element. The halogen (X) element may be one of these elements, or a combination of two or more of them.

[0013] Examples of such sulfide solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiX (wherein "X" represents one or more halogen elements), Li2S-P2S5-P2O5, Li2S-Li3PO4-P2S5, Li3PS4, Li4P2S6, and Li 10GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li7P3S 11 , Li 3.25 P 0.95 S4, Li a P.S. b X c (a solid electrolyte having a crystal phase with an argyrodite-type structure, "X" represents one or more halogen elements.) Among them, a sulfide solid electrolyte containing a crystal phase with an argyrodite-type crystal structure is preferably used because of its excellent ion conductivity. The sulfide solid electrolyte containing a crystal phase with an argyrodite-type crystal structure will be described in detail later.

[0014] The sulfide solid electrolyte of the present invention has an S measured by X-ray photoelectron spectroscopy (hereinafter also referred to as "XPS"). 2p It is preferable that peak 1 is observed in the range of binding energy of 165 eV to 170 eV, and peak 2 is observed in the range of 155 eV to 166 eV. XPS is a measurement method that can analyze the constituent elements and their electronic state of the sample surface by measuring the photoelectron energy generated from the sample surface by irradiating the sample with X-rays. Therefore, the chemical state of the surface of the sulfide solid electrolyte of the present invention can be observed by XPS. As a result of the investigation by the present inventors, it was found that by using a sulfide solid electrolyte in which peak 1 is observed, it is possible to suppress the generation of a resistance layer between the active material and the sulfide solid electrolyte in a high temperature environment. From this viewpoint, peak 1 is the S measured by XPS. 2p The binding energy of is preferably observed at, for example, 165 eV or more, more preferably observed at 165.5 eV or more, and particularly preferably observed at 166 eV or more. On the other hand, the binding energy of peak 1 is preferably observed at, for example, 170 eV or less, more preferably observed at 169.5 eV or less, and particularly preferably observed at 167.5 eV or less. In this specification, "the binding energy is observed at 165 eV or more and 170 eV or less" means that the position of the peak top is observed in the range of 165 eV or more and 170 eV or less. Furthermore, the present inventors have newly discovered that the use of the sulfide solid electrolyte of the present invention in which Peak 1 is observed can solve the problem of a resistance layer being generated between an active material and a sulfide solid electrolyte in a high-voltage state, i.e., in a fully charged state.

[0015] The observation of peak 1 by XPS measurement indicates that the sulfide solid electrolyte of the present invention has a sulfite or a compound having a sulfone group on its surface. In the present invention, it is presumed that the presence of these sulfur oxides on the surface of the sulfide solid electrolyte can suppress the reaction between the active material and the sulfide solid electrolyte even when a solid battery containing the sulfide solid electrolyte is placed in a high-temperature environment or in a high-voltage state, making it difficult for a high-resistance resistive layer to be formed between the active material and the sulfide solid electrolyte.

[0016] In the sulfide solid electrolyte of the present invention, it is preferable that peak 1 is observed with sufficient intensity. In detail, when the peak top intensity of peak 1 observed by XPS measurement is I1 and the peak top intensity of peak 2 is I2, the value of I1 / I2 is preferably 0.017 or more, more preferably 0.025 or more, and particularly preferably 0.035 or more. Here, peak 2 is a peak derived from sulfur atoms of the sulfide solid electrolyte. If the value of I1 / I2 is 0.017 or more, a sufficient amount of sulfite or a compound having a sulfone group is contained, so that the above-mentioned effect can be made more remarkable. When multiple peaks 1 are observed, the maximum of the peak top intensities of those peaks is designated as I1. Similarly, when multiple peaks 2 are observed, the maximum of the peak top intensities of those peaks is designated as I2.

[0017] From the viewpoint of more reliably obtaining the above-mentioned advantages due to the presence of a sulfite or a compound having a sulfone group on the surface of the sulfide solid electrolyte, in the sulfide solid electrolyte of the present invention, the proportion of sulfur (S) elements having a binding energy in the range of 165 eV or more and 170 eV or less is preferably 0.4 at% or more, more preferably 0.5 at% or more, and even more preferably 0.6 at% or more, relative to all elements constituting the sulfide solid electrolyte. In order to maintain high ionic conductivity of the sulfide solid electrolyte, from the viewpoint of reducing the amount of sulfur oxides that can be a resistance factor, the proportion of sulfur (S) elements having a binding energy in the range of 165 eV or more and 170 eV or less is preferably 5 at% or less, more preferably 4 at% or less, and even more preferably 3 at% or less, relative to all elements constituting the sulfide solid electrolyte.

[0018] The sulfide solid electrolyte may lose elemental sulfur from its surface as a result of surface treatment, etc. When elemental sulfur is lost, the argyrodite-type electrolyte decomposes to generate a resistive component, and the ionic conductivity of the sulfide solid electrolyte decreases. In other words, it is advantageous for the sulfide solid electrolyte to have a high concentration of elemental sulfur on its surface. From this viewpoint, in the sulfide solid electrolyte of the present invention, the ratio of sulfur element at a position 100 nm deep from the surface as measured by XPS is defined as Z S1 The ratio of sulfur element at a depth of 5 nm from the surface is Z S2 Then, Z S1 Z for S2 Z is the ratio of S2 / Z S1 The value of Z is preferably 0.6 or more, more preferably 0.65 or more, and even more preferably 0.7 or more. S1 Z for S2 Z S2 / Z S1 It is preferable that the value of is 1 or less. The "depth" mentioned above refers to the depth calculated in terms of SiO2.

[0019] The reason why the ratio of sulfur element at a position 5 nm deep from the particle surface was examined, rather than at the outermost surface of the particle, is that the outermost surface of the particle is significantly affected by external factors such as exposure conditions, etc. At a position 5 nm deep from the particle surface, such influence is small and the characteristics near the surface of the solid electrolyte of the present invention can be exhibited.

[0020] The sulfide solid electrolyte of the present invention is preferably an aggregate of particles. In this case, from the viewpoint of suppressing an increase in resistance due to an increase in surface area and from the viewpoint of facilitating mixing with an active material, the volume cumulative particle size D at 50% cumulative volume by a laser diffraction scattering type particle size distribution measurement method is preferably set to 1.0. 50 is preferably 0.1 μm or more, more preferably 0.4 μm or more, and even more preferably 0.6 μm or more. 50 is preferably 100 μm or less, more preferably 10 μm or less, further preferably 5 μm or less, and particularly preferably 1 μm or less.

[0021] The sulfide solid electrolyte of the present invention has lithium ion conductivity in a solid state. The lithium ion conductivity of the solid electrolyte of the present invention is, for example, preferably 1.0 mS / cm or more at room temperature, i.e., 25° C., more preferably 1.2 mS / cm or more, more preferably 1.3 mS / cm or more, and particularly preferably 1.5 mS / cm or more. The lithium ion conductivity can be measured using the method described in the Examples below.

[0022] As described above, the sulfide solid electrolyte of the present invention preferably contains a crystal structure having a crystal phase of an argyrodite crystal structure. The argyrodite crystal structure is a crystal structure possessed by a group of compounds derived from a mineral represented by the chemical formula: Ag8GeS6. Whether or not the sulfide solid electrolyte has a crystal phase of an argyrodite crystal structure can be confirmed by measurement using X-ray diffraction (hereinafter also referred to as "XRD"). For example, in a diffraction pattern measured by XRD using CuKα1 radiation, the crystal phase of the argyrodite crystal structure shows characteristic diffraction peaks at the positions of 2θ=25.5°±1.0°, 30.0°±1.0°, and 30.9°±1.0°. Depending on the elemental species constituting the sulfide solid electrolyte, in addition to the diffraction peaks, characteristic diffraction peaks may be observed at 2θ=15.3°±1.0°, 18.0°±1.0°, 44.3°±1.0°, 47.2°±1.0°, 51.7°±1.0°, 58.3°±1.0°, 60.7°±1.0°, 61.5°±1.0°, 70.4°±1.0°, and 72.6°±1.0°. The diffraction peaks derived from the argyrodite crystal structure may be identified using, for example, data from PDF No. 00-034-0688.

[0023] When the sulfide solid electrolyte of the present invention includes a crystal structure having a crystal phase of an argyrodite-type crystal structure, the sulfide solid electrolyte has a composition formula (I): Li a P.S. b X c (X is at least one of fluorine (F), chlorine (Cl), bromine (Br) and iodine (I)) is preferred from the viewpoint of improving lithium ion conductivity.

[0024] In the composition formula (I), a, which indicates the molar ratio of Li element, is preferably, for example, 3.0 or more, more preferably 4.0 or more, and particularly preferably 5.0 or more. Meanwhile, the above-mentioned a is preferably, for example, 6.5 or less, more preferably 5.9 or less, and particularly preferably 5.6 or less. When a is in this range, the cubic argyrodite-type crystal structure at around room temperature (25°C) becomes more stable, and lithium ion vacancies can be sufficiently introduced into the structure, and as a result, lithium ion conductivity can be effectively increased.

[0025] In the composition formula (I), b is preferably, for example, 3.5 or more, more preferably 4.0 or more, and particularly preferably 4.2 or more. On the other hand, the above b is preferably, for example, 5.5 or less, more preferably 4.9 or less, and particularly preferably 4.7 or less. When b is within the above range, the argyrodite-type crystal structure at around room temperature (25°C) becomes more stable, and the lithium ion conductivity is effectively increased.

[0026] In the composition formula (I), c is preferably, for example, 0.1 or more, more preferably 1.1 or more, and particularly preferably 1.4 or more. On the other hand, c is preferably, for example, 2.5 or less, more preferably 2.0 or less, and particularly preferably 1.8 or less.

[0027] The sulfide solid electrolyte has the composition formula (II): Li 7-d P.S. 6-d X d The composition represented by the composition formula (II) is a stoichiometric composition of an argyrodite-type crystal phase. In the composition formula (II), X has the same meaning as in the composition formula (I).

[0028] In the composition formula (II), d is preferably, for example, 0.4 or more, more preferably 0.8 or more, and particularly preferably 1.2 or more. On the other hand, d is preferably, for example, 2.2 or less, more preferably 2.0 or less, and particularly preferably 1.8 or less.

[0029] The sulfide solid electrolyte has the composition formula (III): Li 7-d-2e P.S. 6-d-e X d The argyrodite-type crystal phase having the composition represented by composition formula (III) is produced, for example, by a reaction between the argyrodite-type crystal phase having the composition represented by composition formula (II) and P2S5 (diphosphorus pentasulfide).

[0030] In the composition formula (III), e is a value indicating the deviation of the Li2S component from the stoichiometric composition represented by the composition formula (II). For example, e is preferably -0.9 or more, more preferably -0.6 or more, and particularly preferably -0.3 or more. On the other hand, the above e is preferably, for example, (-d+2) or less, more preferably (-d+1.6) or less, and particularly preferably (-d+1.0) or less.

[0031] In the sulfide solid electrolyte, the atomic ratio X / P of the X element to the P element is, for example, preferably greater than 1.0, more preferably 1.1 or more, even more preferably 1.2 or more, and even more preferably 1.4 or more. On the other hand, the atomic ratio X / P is, for example, preferably 2.5 or less, more preferably 2.3 or less, and even more preferably 2.2 or less. The atomic ratio X / P being within the above range further improves the lithium ion conductivity. The atomic ratio X / P can be measured, for example, by inductively coupled plasma atomic emission spectroscopy (ICP atomic emission spectroscopy) or a scanning electron microscope equipped with EDS (SEM-EDS analysis).

[0032] In particular, when the X element includes at least Cl and Br, the atomic ratio (Cl+Br) / P of the total of Cl and Br to P is preferably, for example, greater than 1.0, more preferably 1.1 or more, even more preferably 1.2 or more, and even more preferably 1.4 or more. On the other hand, the atomic ratio (Cl+Br) / P is, for example, preferably 2.5 or less, more preferably 2.3 or less, and even more preferably 2.0 or less. The atomic ratio (Cl+Br) / P within the above range is preferable because it further improves the lithium ion conductivity. The atomic ratio (Cl+Br) / P can be measured by elemental analysis, for example, ICP emission spectroscopy or SEM-EDS analysis.

[0033] The sulfide solid electrolyte is, among the above-mentioned composition formulas (I) to (III), particularly, composition formula (IV) Li 7-d P.S. 6-d Cl d1 Br d2 It is preferable that the formula is represented by the formula: In the composition formula (IV), the total molar ratio d (=d1+d2) of Cl and Br is preferably, for example, greater than 1.0, more preferably 1.2 or more, and particularly preferably 1.4 or more. On the other hand, the total molar ratio d is, for example, preferably less than 2.5, more preferably less than 2.0, particularly preferably 1.8 or less, and even more preferably 1.7 or less. By having the total molar ratio d within the above range, the generation of a different phase can be sufficiently controlled, and the decrease in ion conductivity can be effectively suppressed.

[0034] In the composition formula, the molar ratio of Br to the molar ratio of Cl (d2 / d1) is preferably, for example, 0.1 or more, more preferably 0.3 or more, and particularly preferably 0.5 or more. On the other hand, the molar ratio is preferably, for example, 10 or less, more preferably 5 or less, and particularly preferably 3 or less. By having the molar ratio within the above range, the lithium ion conductivity can be further increased.

[0035] In the composition formula, d1, which indicates the molar ratio of Cl, is preferably, for example, 0.3 or more, more preferably 0.4 or more, and particularly preferably 0.6 or more. On the other hand, the above d1 is preferably, for example, 1.5 or less, more preferably 1.2 or less, and particularly preferably 1.0 or less. When d1 is equal to or more than the lower limit, the lithium ion conductivity can be further increased. On the other hand, when d1 is equal to or less than the upper limit, the above solid electrolyte can be easily obtained.

[0036] In the composition formula, d2, which indicates the molar ratio of Br, is preferably, for example, 0.3 or more, more preferably 0.4 or more, and particularly preferably 0.6 or more. On the other hand, the above d2 is preferably, for example, 1.5 or less, more preferably 1.2 or less, and particularly preferably 1.0 or less. When d2 is equal to or more than the lower limit, a sulfide solid electrolyte is easily obtained. On the other hand, when d2 is equal to or less than the upper limit, lithium ion conductivity can be further increased.

[0037] In any case where the solid electrolyte is represented by any one of the composition formulas (I), (II), (III) and (IV), it is preferable that the X element contains a Br element, since this further improves the lithium ion conductivity.

[0038] The sulfide solid electrolyte of the present invention can be used as an electrode mixture containing the sulfide solid electrolyte and an active material. Alternatively, the sulfide solid electrolyte of the present invention can be used as a solid electrolyte layer containing the sulfide solid electrolyte. By using the sulfide solid electrolyte of the present invention, for example, a solid-state battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer located between the positive electrode layer and the negative electrode layer, and containing the sulfide solid electrolyte of the present invention, can be produced.

[0039] Next, a method for producing the sulfide solid electrolyte of the present invention will be described. The sulfide solid electrolyte of the present invention can be produced by heating the sulfide solid electrolyte powder in an oxygen-containing atmosphere. By heating in an oxygen-containing atmosphere, the surface of the sulfide solid electrolyte particles constituting the sulfide solid electrolyte powder can be oxidized to generate a compound having a sulfite or sulfonic group. From the viewpoint of sufficiently generating a compound having a sulfite or sulfonic group, the oxygen-containing atmosphere preferably contains oxygen at 10% by volume or more, more preferably 15% by volume or more, and even more preferably 20% by volume or more. In addition, from the viewpoint of allowing the reaction to proceed slowly and preferentially reacting the surface without decomposing the inside of the sulfide solid electrolyte particles, the oxygen-containing atmosphere preferably contains oxygen at 50% by volume or less, more preferably 40% by volume or less, and even more preferably 25% by volume or less.

[0040] From a similar viewpoint, the oxygen-containing atmosphere contains an inert gas at preferably 50 vol. % or more, more preferably 60 vol. % or more, even more preferably 75 vol. % or more, and preferably 90 vol. % or less, more preferably 85 vol. % or less, even more preferably 80 vol. % or less.

[0041] In addition, it is preferable that the oxygen-containing atmosphere does not substantially contain water from the viewpoint of preventing decomposition and surface deterioration of the sulfide solid electrolyte caused by moisture. In detail, the dew point of the oxygen-containing atmosphere is preferably −30° C. or less, more preferably −35° C. or less, and further preferably −40° C. or less.

[0042] In view of the above, it is preferable from the viewpoint of economy to use dry air as the oxygen-containing atmosphere.

[0043] The heating temperature of the sulfide solid electrolyte powder is preferably 70° C. or higher, more preferably 80° C. or higher, and even more preferably 90° C. or higher, from the viewpoint of sufficiently proceeding with the oxidation reaction. The heating temperature of the sulfide solid electrolyte powder is preferably 200° C. or lower, more preferably 170° C. or lower, and even more preferably 150° C. or lower, from the viewpoint of suppressing thermal decomposition of the sulfide solid electrolyte. In particular, since a sulfide solid electrolyte containing a crystal phase having an argyrodite-type crystal structure is susceptible to thermal decomposition, it is preferable to heat it at a temperature within the above range.

[0044] The heating time of the sulfide solid electrolyte powder is preferably 30 minutes or more, more preferably 1 hour or more, and even more preferably 3 hours or more from the viewpoint of sufficiently proceeding with the oxidation reaction, and is preferably 18 hours or less, more preferably 12 hours or less, and even more preferably 6 hours or less from the viewpoint of suppressing a decrease in the ionic conductivity of the sulfide solid electrolyte caused by the excessive proceeding of the oxidation reaction.

[0045] When the sulfide solid electrolyte powder is heated under the above conditions to oxidize the surface of the sulfide solid electrolyte particles constituting the powder, the sulfide solid electrolyte obtained can be used in a solid battery to suppress an increase in the direct current resistance of the solid battery even when the solid battery is stored at high temperature or in a high voltage state. On the other hand, the oxidation of the surface of the sulfide solid electrolyte particles constituting the sulfide solid electrolyte powder can cause a decrease in the ionic conductivity of the obtained sulfide solid electrolyte. In the manufacturing method of the present invention, it is preferable to suppress the decrease in the ionic conductivity of the sulfide solid electrolyte as much as possible while fully obtaining the above-mentioned advantages of oxidizing the surface of the sulfide solid electrolyte particles. In detail, it is preferable to perform the heating so that the value of B / A, which is the ratio of B to A, is preferably 0.05 or more, more preferably 0.1 or more, and even more preferably 0.4 or more, when the ionic conductivity of the sulfide solid electrolyte before heating is A (S / cm) and the ionic conductivity of the sulfide solid electrolyte after heating is B (S / cm). In order to adjust the value of B / A within the above range, for example, the composition of the heating atmosphere, the heating temperature, the heating time, etc. may be adjusted.

[0046] There are no particular limitations on the type and composition of the sulfide solid electrolyte powder before heat treatment used in this production method, and the type and composition can be the same as those described above for the sulfide solid electrolyte of the present invention, for example. In addition, the sulfide solid electrolyte powder before the heat treatment had a volume cumulative particle size D 50 is preferably 0.1 μm or more and 100 μm or less, more preferably 0.4 μm or more and 10 μm or less, and further preferably 0.6 μm or more and 5 μm or less.

[0047] The above-described embodiment of the present invention encompasses the following technical ideas. [1] S measured by X-ray photoelectron spectroscopy 2p Peak 1 is observed in the binding energy range of 165 eV to 170 eV, and peak 2 is observed in the binding energy range of 155 eV to 166 eV. The peak top intensity of the peak 1 is I1, When the peak top intensity of the peak 2 is I2, A sulfide solid electrolyte with an I1 / I2 value of 0.017 or greater. [2] S measured by X-ray photoelectron spectroscopy 2p The sulfide solid electrolyte according to [1], wherein a ratio of sulfur (S) elements having a bond energy of 165 eV or more and 170 eV or less is 0.4 at % or more and 5 at % or less with respect to all elements constituting the sulfide solid electrolyte. [3] The sulfide solid electrolyte according to [1] or [2], which contains lithium (Li), phosphorus (P), sulfur (S) and halogen (X). [4] The sulfide solid electrolyte according to any one of [1] to [3], which contains a crystal phase having an argyrodite-type crystal structure. [5] The ratio of sulfur (S) at a depth of 100 nm from the surface measured by X-ray photoelectron spectroscopy is ZS1 The ratio of sulfur (S) element at a depth of 5 nm from the surface is Z S2 Then, Z S1 Z for S2 Z is the ratio of S2 / Z S1 The sulfide solid electrolyte according to any one of [1] to [4], wherein the value of is 0.8 or more. [6] Volume cumulative particle size D at 50% cumulative volume measured by laser diffraction scattering particle size distribution measurement method 50 The sulfide solid electrolyte according to any one of [1] to [5], wherein the average particle size is 0.1 μm or more and less than 100 μm. [7] A method for producing a sulfide solid electrolyte, comprising heating a powder of the sulfide solid electrolyte in an oxygen-containing atmosphere having a dew point of -30°C or lower. [8] The manufacturing method according to [7], wherein the oxygen-containing atmosphere contains 25% by volume or less of oxygen and 75% by volume or more of an inert gas. [9] A manufacturing method described in [7] or [8], in which the mixture is heated to 70°C or higher and 200°C or lower.

[10] A manufacturing method described in any one of [7] to [9], in which heating is performed for 30 minutes or more and 18 hours or less.

[11] The method according to any one of [7] to

[10] , wherein heating is performed such that the ratio of B to A, that is, B / A, is 0.05 or more, where A (S / cm) is the ionic conductivity of the sulfide solid electrolyte before heating and B (S / cm) is the ionic conductivity of the sulfide solid electrolyte after heating.

[12] An electrode mixture comprising the sulfide solid electrolyte according to any one of [1] to [6] and an active material.

[13] A solid electrolyte layer comprising the sulfide solid electrolyte according to any one of [1] to [6].

[14] A solid-state battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer located between the positive electrode layer and the negative electrode layer, the solid-state battery containing the sulfide solid electrolyte according to any one of [1] to [6]. EXAMPLES

[0048] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.

[0049] [Examples 1 to 4] Composition formula Li 5.4 P.S. 4.4 Br 0.8 Cl 0.8 A sulfide solid electrolyte having an oxidized surface was produced by heating 5 g of a sulfide solid electrolyte powder containing a crystal phase having an argyrodite crystal structure using a hot plate in a dry air atmosphere in a glove box. The heating conditions were as shown in Table 2. Example 5 Composition formula Li 5.4 P.S. 4.4 Br 0.8 Cl 0.8 A sulfide solid electrolyte with an oxidized surface was produced by heating 5 g of sulfide solid electrolyte powder containing a crystal phase having an argyrodite crystal structure in a tubular furnace under a dry air atmosphere in an air cylinder (Suzusho General Gas Center Co., Ltd., filling pressure 14.7 MPa (35°C), dew point -40°C or less). The heating conditions were as shown in Table 2.

[0050] Comparative Example 1 The same sulfide solid electrolyte powder as in Example 1 was used, and the powder was not heat-treated, but was used as it is to prepare the sulfide solid electrolyte of Comparative Example 1.

[0051] Comparative Example 2 The same sulfide solid electrolyte powder as in Example 1 was used, but instead of heating the powder, a treatment was performed in which the powder was exposed to dry air at room temperature of 25° C. to obtain a sulfide solid electrolyte of Comparative Example 2. The dew point of the dry air and the treatment time in the treatment were as shown in Table 2.

[0052] 〔evaluation〕 For the sulfide solid electrolytes produced in each Example and Comparative Example, 50 The following measurements were performed and the following evaluations were carried out.

[0053] [XPS measurement and analysis] The surface of the sulfide solid electrolyte was measured using a VersaProbeIII XPS device manufactured by ULVAC-PHI, Inc. The measurement conditions were as follows: Excitation X-ray: Monochrome AlKα radiation (1486.7 eV) Output: 50W X-ray diameter: 200μm Pass Energy: 26eV Photoelectron escape angle: 45° (Ar ion etching conditions) Acceleration voltage: 2kV Sputter area: 2mm x 2mm Etching speed: 8.0nm / min in SiO2 equivalent The peak intensity reading and quantitative value calculation were performed using data analysis software (ULVAC-PHI "MultiPak Ver 9.9"). The background mode used was Shirley. Charging correction was performed by setting the binding energy of the hydrocarbon (C-H) peak in the C1s spectrum to 284.8 eV.

[0054] <Calculation method for peak top intensity ratio I1 / I2 between peak 1 and peak 2> The peak top intensity I1 of peak 1 and the peak top intensity I2 of peak 2 were read using the peak information acquisition function "FWHM / Area" installed in the data analysis software (ULVAC-PHI "MultiPak Ver 9.9"). The background (BG) ranges when acquiring peak information for Peak 1 and Peak 2 were as shown in Table 1. The "Hight" values ​​were used for intensities I1 and I2.

[0055] [Table 1] <S in the range of 165 eV to 170 eV 2p How to calculate the percentage of sulfur elements with bond energy of > From the spectrum obtained under the above measurement conditions, the integral value of the peak of each measured element was calculated, and based on this, S in the range of 165 eV to 170 eV was calculated. 2p The proportion of sulfur elements having a bond energy of

[0056] [Z S1 and Z S2 〕 For the solid electrolytes obtained in each of the Examples and Comparative Examples, the ratios of lithium (Li), carbon (C), oxygen (O), phosphorus (P), sulfur (S), and halogen (Ha) were measured at depths of 100 nm and 5 nm from the particle surface under the above-mentioned conditions using the XPS device. The ratio of sulfur (S) element at a depth of 100 nm from the surface was defined as Z S1 , and the ratio of sulfur (S) element at a depth of 5 nm from the surface is Z S2 The results are shown in Table 2.

[0057] [Ionic Conductivity] The solid electrolyte powder obtained in each Example and Comparative Example was heated at about 6 t / cm in a glove box purged with sufficiently dried Ar gas (dew point -60°C or less). 2 A load of 10 ... In addition, the ratio of B to A, B / A, was calculated by dividing the obtained ionic conductivity (B) by the ionic conductivity (A) of the sulfide solid electrolyte of Comparative Example 1 that was not subjected to treatment such as heating.

[0058] [DC internal resistance after float (DCIR)] (material) The positive electrode active material powder is a ternary layered compound, LiNi 0.5 Co 0.2 Mn 0.3O2 (NCM) powder (D 50 = 6.7 μm) was used as the negative electrode active material, and graphite (Gr) powder (D 50 = 20 μm) was used, and the sulfide solid electrolytes obtained in each of the examples and comparative examples were used as solid electrolyte powders. The positive electrode mixture powder was prepared by mixing the positive electrode active material powder, the solid electrolyte powder, and a conductive additive (acetylene black) in a mass ratio of 60:37:3 in a mortar, and then uniaxially press-molded at 20 MPa to obtain positive electrode mixture pellets. The negative electrode composite powder was prepared by mixing graphite powder and standard solid electrolyte powder that had not been subjected to heat treatment (that is, the sulfide solid electrolyte powder of Comparative Example 1) in a mortar in a mass ratio of 64:36.

[0059] (Battery Construction) The lower opening of a polypropylene cylinder (opening diameter 10.5 mm, height 18 mm) with openings at the top and bottom was blocked with a positive electrode (made of SUS), and a positive electrode composite pellet was placed on the positive electrode. Standard solid electrolyte powder that had not been heat-treated was placed on top of that, and uniaxial pressing was performed at 180 MPa to form a positive electrode composite and a solid electrolyte layer. The negative electrode composite powder was then placed on top of that, and the cylinder was blocked with a negative electrode (made of SUS) and uniaxial pressing was performed at 550 MPa to create a dice battery with a three-layer structure consisting of a positive electrode composite approximately 100 μm thick, a solid electrolyte layer approximately 300 μm thick, and a negative electrode composite approximately 20 μm thick.

[0060] (Battery evaluation) Using the dice battery prepared as described above, an initial charge / discharge test, a float test, and a direct current internal resistance (DCIR) measurement were carried out as follows. The battery was placed in an environmental tester in which the environmental temperature for charging and discharging the battery had been set to 25° C., and prepared for charging and discharging, and was left to stand so that the battery temperature became the environmental temperature. The battery was charged and discharged at 1 mA at 1 C. First, the battery was charged at a constant current and constant potential at 0.1 C up to 4.5 V, and then discharged at a constant current of 0.1 C up to 2.5 V, which was repeated three times to perform an initial charge and discharge test. Next, the battery was charged at a constant current and constant potential at 0.1C up to 4.5V with the environmental temperature for charging and discharging being 25°C, and then a float test was performed in which the battery was charged and discharged at a constant voltage of 4.5V for 110 hours with the environmental temperature for charging and discharging being 60°C. The battery was then charged and discharged at an environmental temperature of 25°C for 4 hours, after which it was left to cool sufficiently, and then discharged at a constant current of 0.1 C to 2.5 V, after which it was charged at a constant current and constant potential of 0.1 C to 3.7 V. From a state where the battery voltage was 3.7 V, it was discharged at 10 mA for 10 seconds, and the direct current internal resistance (DCIR) was measured from the potential difference before and after the end of discharge.

[0061] These results are shown in Table 2. Furthermore, XPS spectra of the sulfide solid electrolytes obtained in Example 2 and Comparative Examples 1 and 2 in the binding energy ranges of 165 eV to 170 eV and 158 to 170 eV are shown in FIG. In addition, unmeasured data in Comparative Example 2 is indicated in Table 2 as "-".

[0062] [Table 2]

[0063] As is clear from Table 2, the sulfide solid electrolyte of each Example had a low DCIR after float at an ambient temperature of 60° C. and a voltage of 4.5 V, and it was found that the increase in DC resistance of the solid-state battery was suppressed when stored under high temperature and high voltage conditions. In each Example, the ionic conductivity of the sulfide solid electrolyte was slightly reduced by the heat treatment, but the amount of reduction was not of practical concern.

Claims

1. S measured by X-ray photoelectron spectroscopy 2p Peak 1 is observed in the binding energy range of 165 eV or more and 170 eV or less, and peak 2 is observed in the binding energy range of 155 eV or more and 166 eV or less, The peak top intensity of the peak 1 is I 1 year, The peak top intensity of the peak 2 is I 2 When I 1 / I 2 The sulfide solid electrolyte has a value of 0.017 or more.

2. S measured by X-ray photoelectron spectroscopy 2p 2. The sulfide solid electrolyte according to claim 1, wherein the ratio of sulfur (S) elements having a binding energy of 165 eV or more and 170 eV or less is 0.4 at% or more and 5 at% or less with respect to all elements constituting the sulfide solid electrolyte.

3. The sulfide solid electrolyte according to claim 1, comprising lithium (Li), phosphorus (P), sulfur (S) and halogen (X).

4. The sulfide solid electrolyte according to claim 1 , comprising a crystalline phase having an argyrodite-type crystal structure.

5. The ratio of sulfur (S) element at a depth of 100 nm from the surface measured by X-ray photoelectron spectroscopy is Z S1 The ratio of sulfur (S) element at a depth of 5 nm from the surface is Z S2 Then, Z S1 Z for S2 Z is the ratio of S2 / Z S1 The sulfide solid electrolyte according to claim 1, wherein the value of is 0.6 or more.

6. Volume cumulative particle size D at 50% cumulative volume measured by laser diffraction scattering particle size distribution measurement method 50 The sulfide solid electrolyte according to claim 1, wherein the particle size is 0.1 μm or more and 100 μm or less.

7. A method for producing a sulfide solid electrolyte, comprising heating a powder of the sulfide solid electrolyte in an oxygen-containing atmosphere having a dew point of −30° C. or lower.

8. The method according to claim 7 , wherein the oxygen-containing atmosphere contains 50% by volume or less of oxygen and 50% by volume or more of an inert gas.

9. The method according to claim 7 or 8, wherein the heating is performed at 70°C or higher and 200°C or lower.

10. The method according to claim 7 or 8, wherein heating is performed for 30 minutes or more and 18 hours or less.

11. 9. The method according to claim 7 or 8, wherein heating is performed such that a ratio of B to A, that is, a value of B / A, is 0.05 or more, where A (S / cm) is an ionic conductivity of the sulfide solid electrolyte before heating and B (S / cm) is an ionic conductivity of the sulfide solid electrolyte after heating.

12. An electrode mixture comprising the sulfide solid electrolyte according to claim 1 and an active material.

13. A solid electrolyte layer comprising the sulfide solid electrolyte according to claim 1 .

14. A solid-state battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer located between the positive electrode layer and the negative electrode layer, the solid-state battery containing the sulfide solid electrolyte according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method of modifying solid electrolyte including argyrodite type crystal structure

    JP2020075855A

  • Sulfide-based solid electrolyte and method for producing the same, solid electrolyte layer, and lithium-ion secondary battery

    JP7092248B1

  • Sulfide-based solid electrolyte particles

    WO2019176895A1